False Sense of Security: Racial Segregation in Moonrise Over New Jessup (2023) by Jamila Minnicks (English Language and Literature (JELL), 2026)
This research analyzes racial segregation in Moonrise Over New Jessup (2023) by Jamila Minnicks using Critical Race Theory (CRT) as proposed by Delgado & Stefancic and Gramsci’s concept of Hegemony. The purpose of this research is to examine how racial segregation, which is accepted by the majority of Black people, is portrayed in the novel and how this condition constructs a false sense of security. The method used in this study is qualitative descriptive, focusing on textual evidence from the novel. The findings indicate that the racial segregation accepted by the majority of Black people is depicted in three main forms: residential segregation, school segregation, and workplace segregation. The acceptance of this segregation practice is influenced by fear of racial violence and social familiarity within the same community, which leads to the construction of false sense of security. In addition, this study finds two different responses from Black characters, that are acceptance and resistance toward the dominant ideology.
Keywords: Racial Segregation; False Sense of Security; Critical Race Theory; Hegemony